Strategi Peningkatan Literasi Membaca Siswa Sekolah Dasar Melalui Gerakan Priority Reading Optimistic (PRO) - Rahmalia, Indah; Yenti, Fepryna; Istiqlal, Abdul; Khairani, Majidah (CV. Kurnia Grup, 2026)
Many elementary school students experience difficulties in recognizing letters, reading by spelling, reading fluently, and understanding simple reading texts, which affect their overall learning outcomes. Therefore, an effective reading assistance program is needed to improve students’ reading literacy skills gradually and continuously. This study aimed to describe the implementation of the Priority Reading Optimistic (PRO) Movement in improving elementary school students’ reading literacy skills at SD Negeri 21 Pasir Tinggi. The study was motivated by the low reading ability of students, as indicated by difficulties in recognizing letters, reading with spelling, slow reading, and low comprehension of simple texts. This research employed a descriptive qualitative approach supported by simple quantitative data. The research subjects consisted of 31 students who experienced reading difficulties. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that the implementation of the Priority Reading Optimistic (PRO) Movement had a positive impact on improving students’ reading literacy skills. Reading assistance was conducted gradually through grouping students based on their reading abilities, routine reading exercises, individual mentoring, and interactive learning activities. After the implementation of the program, the number of students experiencing reading difficulties decreased in several indicators, such as letter recognition, reading by spelling, pronunciation errors, and slow reading. In addition, students’ reading fluency and comprehension of simple texts also improved significantly. The program not only improved students’ reading abilities but also increased their learning motivation and self-confidence in reading activities.